Cartilage/bone interface fabricated under perfusion: Spatially organized commitment of adipose‐derived stem cells without medium supplementation. Issue 6 (21st November 2018) - Baumgartner, Walter; Otto, Lukas; Hess, Samuel C.; Stark, Wendelin J.; Märsmann, Sonja; Bürgisser, Gabriella Meier; Calcagni, Maurizio; Cinelli, Paolo; Buschmann, Johanna
Abstract: Tissue engineering of an osteochondral interface demands for a gradual transition of chondrocyte‐ to osteoblast‐prevailing tissue. If stem cells are used as a single cell source, an appropriate cue to trigger the desired differentiation is the use of composite materials with different amounts of calcium phosphate. Electrospun meshes of poly‐lactic‐co‐glycolic acid and amorphous calcium phosphate nanoparticles (PLGA/aCaP) in weight ratios of 100:0; 90:10, 80:20, and 70:30 were seeded with human adipose‐derived stem cells (ASCs) and cultured in DMEM without chemical supplementation. After 2 weeks of static cultivation, they were either further cultivated statically for another 2 weeks (group 1), or placed in a Bose® bioreactor with a flow rate per area of 0.16 mL cm −2 min −1 (group 2). Markers for stem cell criteria, chondrogenesis, osteogenesis, adipogenesis and angiogenesis were analyzed by quantitative real‐time PCR. Cell distribution, Sox9 protein expression and proteoglycans were assessed by histology. In group 2 (perfusion culture), chondrogenic Sox9 was upregulated toward the cartilage‐mimicking side compared to pure PLGA. On the bone‐mimicking side, Sox9 experienced a downregulation, which was confirmed on the protein level. Vice versa, expression of osteocalcin was upregulated on the bone‐mimicking side, while it was unchanged on the cartilage‐mimicking side. In group 1 (static culture), CD31 was upregulated in the presence of aCaP compared to pure PLGA, whereas Sox9 and osteocalcin expression were not affected. aCaP nanoparticles incorporated in electrospun PLGA drive the differentiation behavior of human ASCs in a dose‐dependent manner. Discrete gradients of aCaP may act as promising osteochondral interfaces. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1833–1843, 2019. Abstract : A gradient‐based nanocomposite (PLGA/aCaP) was seeded with human ASCs and cultivated in a perfusion flow bioreactor without supplementation. Gene expression of osteocalcin increased toward the bone‐mimicking side, while gene expression of Sox9 increased toward the cartilage‐mimicking side. Under static cultivation (control), these typical marker genes for osteogenesis (osteocalcin) and chondrogenesis (Sox9) were not influenced by the presence of amorphous calcium phosphate.